The Role of Rationality and Reason: A Critical Study of the Thought of Mustafa Akyol - Alfian Fadhilah (International Journal of Sociology of Religion, 2025)
In response to the challenges of modernity in the Muslim world, Mustafa Akyol, a prominent intellectual, has called for a revival of rationalism within Islam. This study offers a critical analysis of his intellectual vision. Two of Akyol’s works, Reopening Muslim Minds and Islam Without Extremes, are examined in this article using a qualitative literature review method with a historical-philosophical analytical approach. The study situates Akyol’s ideas within the broader trajectory of rationalism, tracing its development from classical Islamic theology (the Mu‘tazilites and Ibn Rushd), Greek philosophy, and the Western Enlightenment. The findings indicate that while Akyol successfully revitalizes discourse on the importance of reason, freedom, and tolerance in Islam through a compelling and accessible narrative, his thesis contains several fundamental weaknesses. These include historical reductionism in portraying the theological contestation between the Mu‘tazilites and the Ash‘arites, misrepresentation of Ash‘arite theological doctrines—one of his primary targets of critique—and a tendency toward uncritical acceptance of classical liberal frameworks. Critical analysis further reveals that Akyol’s failure to operate within an epistemological framework recognized by orthodox Islamic tradition renders his reform project less persuasive for the very audience he seeks to engage. The article concludes that Akyol’s most significant contribution lies in his role as a catalyst for public discourse; however, the effectiveness and diagnostic accuracy of his work as a coherent project of theological reform remain highly debatable.